2013
DOI: 10.1890/12-1819.1
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between conventional and organic farming for biocontrol services across the landscape

Abstract: While the area of organic crop production increases at a global scale, the potential interactions between pest management in organic and conventionally managed systems have so far received little attention. Here, we evaluate the landscape-level codependence of insecticide-based and natural enemy-based pest management using a simulation model for parasitoid-host interactions in landscapes consisting of conventionally and organically managed fields. In our simulations conventional management consists of broad-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
3
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 38 publications
(37 reference statements)
3
57
3
2
Order By: Relevance
“…However, due to lower yields, larger surfaces are needed to maintain food production under OF, hence the net balance between positive and negative impacts is still debated [12,15,16]. OF effects at the field level may further depend on surrounding landscapes [4,17,18]. Bengtsson et al [19] proposed that OF benefits on biodiversity should increase linearly with agriculture intensification at the landscape scale.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to lower yields, larger surfaces are needed to maintain food production under OF, hence the net balance between positive and negative impacts is still debated [12,15,16]. OF effects at the field level may further depend on surrounding landscapes [4,17,18]. Bengtsson et al [19] proposed that OF benefits on biodiversity should increase linearly with agriculture intensification at the landscape scale.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these authors determined that these effects were due to insecticides by also comparing treated and untreated conventional fields and finding that like organic farms, insecticide-untreated fields had higher predator-prey ratios than insecticide-treated fields. Moreover, effects of insecticide input on bio-control can go beyond farm level (Bianchi, Ives, and Schellhorn 2013). For example, crop pest abundance increases with the proportion of harvested cropland treated with insecticides in Midwestern United States (Meehan et al 2011), although this relationship can vary greatly between years (Larsen 2013).…”
Section: Local Effectsmentioning
confidence: 99%
“…Though classified as 'simple' due to high amounts of cropland, a closer evaluation showed that biodiversity enhancement was mainly driven by the amount of cropland under organic management. Likewise, a simulation study found that a minimum proportion of organically managed farms in the landscape was needed to sustain parasitoid populations and to provide biocontrol services (Bianchi, Ives, and Schellhorn 2013). Furthermore, landscapes with a high amount of cropland, but also with heterogeneous crop management, may result in attenuation of negative interactions among natural enemies, allow coexistence, and increase regional diversity.…”
Section: Standardizing and Refining Landscape Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…conventionally managed systems have to date received little attention [38]. Organic agriculture improves biodiversity at the field level, but potential interactions with the surrounding landscape and the potential effects on ecosystem services are less well known.…”
Section: Impact Of Organic Farming On Biodiversitymentioning
confidence: 99%